2012
DOI: 10.1186/1475-2891-11-27
|View full text |Cite
|
Sign up to set email alerts
|

Role of nutritional status in predicting quality of life outcomes in cancer – a systematic review of the epidemiological literature

Abstract: Malnutrition is a significant factor in predicting cancer patients’ quality of life (QoL). We systematically reviewed the literature on the role of nutritional status in predicting QoL in cancer. We searched MEDLINE database using the terms “nutritional status” in combination with “quality of life” together with “cancer”. Human studies published in English, having nutritional status as one of the predictor variables, and QoL as one of the outcome measures were included. Of the 26 included studies, 6 investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(188 citation statements)
references
References 34 publications
7
163
0
9
Order By: Relevance
“…In a systematic review, Lis et al 6 found an association between weight loss and swelling. In patients with advanced hnc who undergo surgery, lymph node stage, non-radical resection margins, and occurrence of major postoperative complications have been demonstrated to affect disease-specific survival in men and women alike.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review, Lis et al 6 found an association between weight loss and swelling. In patients with advanced hnc who undergo surgery, lymph node stage, non-radical resection margins, and occurrence of major postoperative complications have been demonstrated to affect disease-specific survival in men and women alike.…”
Section: Discussionmentioning
confidence: 99%
“…The obstacles to weight maintenance result not only from the cancer itself but also from its therapy: surgery, radiotherapy, and chemotherapy, which also lead to additional complications (for example, in oral intake) 2,5 . The incidence of malnutrition in cancer patients ranges between 40% and 80%, and the prevalence ranges from 50% to 80% depending on tumour type, tumour location, stage of disease, treatment received, and the nutrition assessment method used 6 . Malnutrition and nutrition deficits all have a significant effect on mortality, morbidity, and quality of life in patients with hnc [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…It is a multidimensional concept which addresses various areas related to physical, emotional, sexual and functioning (Victorson et al, 2007). A systematic review demonstrated a strong association between nutritional status and health related quality of life in the cancer population (Lis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising that weight loss has a negative impact on QoL, considering loss of muscle mass (sarcopenia) is a major cause of fatigue (81,82) and weight loss is associated with reduced functional ability (78) . Nutrition-related symptoms associated with chemotherapy such as nausea, vomiting, fatigue and constipation negatively impact the patients' wellbeing, thus reducing their QoL (83,84) . Appetite loss and fatigue, could be a cause or a consequence of malnutrition in cancer patients and lead to subsequent deterioration in global health status and functional scales, which might result in dose-limiting toxicities or suspension of chemotherapy treatment, and ultimately increased morbidity and mortality (7,64,85,86) .…”
Section: Quality Of Lifementioning
confidence: 99%